Can a place of living of elementary school students determine their health habit? - Larisa Gavran; Vedada Čerim; Nino Hasanica (Medicinski glasnik, 2018)
Aim: To determine dietary habits of elementary school students in relation to a place of living and socioeconomic status of the family. Methods: A prospective study conducted in the Primary Health Center Zenica involved five family medicine teams in urban and five in rural settlement during 2015. Elementary school students aged 10-16 were interviewed by random selection using a questionnaire on the socioeconomic status of parents and nutritional habits of adolescents. Results: The survey involved 199 respondents, 103 from rural and 96 from urban area. There were significantly more pupils from employed parents who consumed non-carbonated drinks. Students from urban areas more likely consumed fruit every day than children from rural areas. More than half of the respondents did not or rarely consumed vegetables, in this case the village pupils, who consumed much less milk. It would be expected that rural students were more likely to consume fruits, vegetables and milk due to easier access to these foods in the countryside, but the results of this research did not confirm this assumption. Conclusion: Changes in traditional family functioning (lower income, unemployment) could be linked with lifestyle changes (low consumption of fruits and vegetables, low consumption of milk both in rural and urban areas, consumption of carbonated drinks), especially in families in rural areas.
Keywords: adolescents; dietary habits; milk; socio economic status; vegetables